Corporate governance and company Attributes on the financial reporting timeless: Evidence from listed companies in Bursa Efek Indonesia - Pratama, Ikbar (2015)
Timeliness and corporate governance are considered a critical and important factors which affect the usefulness of information made available to external users. The purpose of this study is to examine the effect of corporate governance (Board of Director and Audit Committee size) and company attributes (Company Size and Company Sector) that affect financial reporting timeliness of the listed companies on the Bursa Efek Indonesia (BEI) in the Republik Indonesia. The study applied the agency theory and formulated four hypotheses that guided the analysis. The study sample comprised of 175 listed companies on the BEI. To achieve the study's objectives, the collected data were analysed by using SPSS version 19. This study finds a positive relationship but not significant between company size and financial reporting timeliness, but a negative relationship between board of directors size, audit committee size and company sector with financial reporting timeliness. However, the size of board of directors is not significant. The study also recommends the steps to improve financial reporting timeliness in Bursa Efek Indonesia